DEFERRED TAX ASSETS IN FOCUS: ANALYZING THEIR EFFECT ON EARNINGS MANAGEMENT WITH AUDIT QUALITY AS A KEY MODERATOR - Benny Oktaviano; Dhani Rosjadi; Dian Sulistyorini Wulandari (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the effect of Deferred Tax Assets (DTA) on Earnings Management and assess the role of Audit Quality as a moderating variable. The research object comprises manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative approach was employed, using panel regression with a Random Effects model, selected based on Hausman and Lagrange Multiplier tests. The results indicate that DTAs have a positive and significant effect on Earnings Management, suggesting that firms use DTA flexibility to manipulate earnings. However, the interaction test between DTA and Audit Quality yields a negative but statistically insignificant coefficient, indicating that Audit Quality does not significantly moderate the relationship between DTA and Earnings Management. These findings imply that, although high-quality auditors are expected to constrain earnings management practices, their moderating role was not empirically supported in this sample.